A resin composition, a metal-clad laminate, and applications thereof
Patent Information
- Application Number
- CN202510536236.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]尽管填充无机填料对降低基板的热膨胀系数、改善板材尺寸稳定性是有益的;但是,当无机填料的填充量低时,对于基板尺寸稳定性的改善效果并不明显;当无机填料的填充量高时,容易导致包含其的树脂组合物、预浸料的流动性降低,加工性能不好,而且制备得到的板材边缘处存在沟壑等明显的表观缺陷,影响印制电路板中的应用
[0082](1)本发明提供的树脂组合物中,通过特定结构的苯并噁嗪树脂的设计及其与固化剂、环氧树脂、填料的相互作用,协同提升固化物的交联密度,使所述树脂组合物及包含其的预浸料、层压板、覆金属箔层压板的热膨胀系数低,玻璃化转变温度高,流动性好,尤其有效改善了填料高填充条件下的流动性,具有优异的加工性能,介电性能优良,并避免板材边缘出现沟壑等表观缺陷。
Smart Images

Figure CN122978653A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of printed circuit board technology, specifically relating to a resin composition, a metal foil laminate, and their applications. Background Technology
[0002] In recent years, electronic devices have been continuously developing towards higher frequencies, smaller sizes, larger information capacities, higher densities, and higher performance. This has placed higher performance demands on printed circuit boards (PCBs), which are the main support for electronic components. For example, they need to have excellent dimensional stability, reliability, and heat resistance, while also maintaining good dielectric properties. Since the substrate largely determines the performance of PCBs, there is an urgent need to develop a new generation of substrate materials.
[0003] Epoxy resin is one of the most widely used materials in substrates, possessing excellent heat resistance, chemical stability, mechanical properties, processability, and cost advantages. To further improve the dimensional stability and mechanical strength of epoxy resin-containing substrates, inorganic fillers are often added. For example, JP2014148562A discloses a curable resin composition comprising a multifunctional epoxy resin, an active ester compound, a benzoxazine compound, and a filler. By controlling the components in the resin composition within appropriate ranges, a cured product with a low coefficient of thermal expansion and good heat resistance and dielectric properties can be obtained. CN102276961A discloses a halogen-free epoxy resin composition comprising, by weight: (a) epoxy resin: 40-80 parts; (b) cyanate ester resin: 1-15 parts; (c) benzoxazine resin: 10-45 parts; (d) aromatic amine compound: 5-30 parts; (e) inorganic filler; with the total amount of components a, b, c, and d being 100 parts, the content of component e is: the total amount of the first four components is 70-150:100; the resin composition has good heat resistance, low coefficient of thermal expansion, and excellent flame retardancy, and can meet the requirements of printed circuit board substrates.
[0004] While inorganic fillers are beneficial for reducing the coefficient of thermal expansion and improving the dimensional stability of substrates, the effect on dimensional stability is not significant when the filler content is low. Conversely, high filler content can lead to reduced flowability of the resin composition and prepreg containing the filler, resulting in poor processing performance and noticeable surface defects such as grooves at the edges of the prepared substrate, thus affecting its application in printed circuit boards. Therefore, developing resin materials with low coefficients of thermal expansion and good flowability, as well as substrates containing them, is a pressing issue in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a resin composition, a metal foil-coated laminate, and their applications. Through the design of a specific structure of a multifunctional benzoxazine resin and its compounding with epoxy resin, curing agent, and filler, the resin composition and the prepreg, laminate, and metal foil-coated laminate containing it possess low coefficient of thermal expansion, high glass transition temperature, and excellent processing fluidity, avoiding surface defects such as grooves at the edges of the substrate. At the same time, it exhibits excellent dielectric properties, fully meeting the application requirements of high-performance substrate materials.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a resin composition comprising, by weight, the following components:
[0008]
[0009] The benzoxazine resin has the structure shown in Formula I:
[0010]
[0011] In Formula I, R1 and R2 are each independently selected from any one of the following: single-bonded, unsubstituted or halogen-substituted C1-C12 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, or C10) straight-chain or branched alkylene groups, C3-C12 (e.g., C4, C5, C6, C7, C8, C9, or C10) cycloalkylene groups, -O-, -S-, carbonyl, sulfone, and sulfoxide groups. When R2 is a single bond, it represents two benzoxazine rings directly linked by a single bond; when R1 is a single bond, it represents two benzene rings directly linked by a single bond.
[0012] In Formula I, n is 1-12, for example, it can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12.
[0013] The resin composition provided by this invention employs a benzoxazine resin and a curing agent to synergistically cure an epoxy resin. The benzoxazine resin has the structure shown in Formula I, and is a polyphenol-polyamine type multifunctional benzoxazine resin. Its molecular structure contains numerous oxazine and benzene rings, exhibiting high rigidity, which increases crosslinking density, raises the glass transition temperature of the cured product, significantly improves fluidity, and reduces the coefficient of thermal expansion. The curing agent promotes the ring-opening reaction of the benzoxazine resin, and the two synergistically cure the epoxy resin, increasing the crosslinking density of the cured product. This invention, through the design of a specific benzoxazine resin structure and its interaction with the curing agent, epoxy resin, and filler, results in a resin composition and its containing prepregs, laminates, and metal foil-coated laminates exhibiting low coefficients of thermal expansion, high glass transition temperatures, and good fluidity. It particularly improves fluidity under high filler loading, resulting in excellent processing performance, superior dielectric properties, and effectively preventing surface defects such as grooves at the edges of the substrate, thus fully meeting the application requirements of high-performance substrate materials.
[0014] In the resin composition provided by the present invention, the epoxy resin is in the form of 10-20 parts by weight, for example, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts or 19 parts, and specific values between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0015] The curing agent is in the range of 5-15 parts by weight, for example, 6, 7, 8, 9, 10, 11, 12, 13 or 14 parts, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0016] The benzoxazine resin is in the range of 1-10 parts by weight, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, and specific values between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0017] The mass fraction of the filler is 65-80 parts, for example, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts or 80 parts, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0018] The terms "parts" and "parts by weight" used in this invention are calculated based on solid content and do not include solvents, dispersants, etc.
[0019] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0020] In this invention, the C1-C12 straight-chain or branched alkylene groups can be straight-chain or branched alkylene groups of C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, or C12, specifically, they are divalent groups formed by the loss of one H atom by C1-C12 straight-chain or branched alkyl groups.
[0021] In this invention, the C3-C12 cycloalkyl group can be a C3, C4, C5, C6, C7, C8, C9, C10, or C12 cycloalkyl group, specifically a divalent group formed by the loss of one H atom from a C3-C12 cycloalkyl group, including a monocycloalkyl group or a polycycloalkyl group.
[0022] In this invention, the halogen includes F, Cl, Br or I, etc.; the halogen-substituted C1-C12 straight-chain or branched alkylene groups represent divalent groups formed by replacing at least one H atom in the C1-C12 straight-chain or branched alkylene groups with a halogen (e.g., F, Cl, Br or I).
[0023] Preferably, the benzoxazine resin has the structure shown in Formula II:
[0024]
[0025] Among them, R1, R2, and n have the same limited range as Equation I.
[0026] Preferably, R1 is selected from any one of single-bonded, unsubstituted or halogenated C1-C6 straight-chain or branched alkylene groups, or sulfone groups; more preferably, single-bonded, unsubstituted or halogenated R1 is selected from any one of these groups. *-CH2-* or Here, -* represents the linking site of a group.
[0027] Preferably, R2 is selected from any one of single bonds, unsubstituted or halogenated C1-C6 straight-chain or branched alkylene groups, C5-C12 cycloalkylene groups, -O-, and -S-, and more preferably single bonds, *-CH2-* ... -O-; where -* represents the linking site of the group.
[0028] Preferably, the epoxy resin includes any one or a combination of at least two of the following: bisphenol A type epoxy resin, bisphenol F type epoxy resin, phosphorus-containing epoxy resin, isocyanate modified epoxy resin, phenolic epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, naphthalene-containing epoxy resin, and alicyclic epoxy resin.
[0029] Preferably, the phenolic epoxy resin includes any one or a combination of at least two of the following: biphenyl phenolic epoxy resin, bisphenol A phenolic epoxy resin, bisphenol F phenolic epoxy resin, phenolic epoxy resin, cresol phenolic epoxy resin, and naphthol phenolic epoxy resin.
[0030] Preferably, the isocyanate-modified epoxy resin includes MDI (diphenylmethane diisocyanate)-modified epoxy resin.
[0031] Preferably, the curing agent includes any one or a combination of at least two of phenolic curing agents, cyanate ester curing agents, reactive ester curing agents, polyphenylene ether curing agents, maleimide curing agents, acid anhydride curing agents, and amine curing agents. More preferably, it includes any one or a combination of at least two of phenolic curing agents, reactive ester curing agents, and amine curing agents.
[0032] Preferably, the phenolic curing agent includes phenolic resin, and more preferably includes any one or a combination of at least two of bisphenol A type phenolic resin, phosphorus-containing phenolic resin, phenolic resin, biphenyl type phenolic resin, dicyclopentadiene type phenolic resin, and naphthol-containing phenolic resin.
[0033] Preferably, the filler comprises any one or a combination of at least two of the following: silica, hollow filler, alumina, mica, quartz powder, clay, calcium oxalate, calcium carbonate, barium sulfate, magnesium oxide, zinc oxide, boron nitride, aluminum nitride, silicon nitride, aluminum hydroxide, titanium dioxide, glass powder, talc, silicon carbide, barium sulfate, barium titanate, strontium titanate, and calcium silicate.
[0034] Preferably, the silicon dioxide can be any one or a combination of at least two of crystalline silicon dioxide, molten silicon dioxide, amorphous silicon dioxide, spherical silicon dioxide, and hollow silicon dioxide.
[0035] This invention relates to the average particle size (D) of the filler. 50 There are no particular limitations; from a dispersibility perspective, the average particle size (D) of the filler is... 50 The preferred particle size distribution (PPD) is 0.01-20 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, or 18 μm, as well as specific values between the above values. For space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values included in the range, but 0.01-10 μm is further preferred. Different types of fillers with different particle size distributions or different average particle sizes can be used alone or in combination as needed.
[0036] For example, the particle size of the filler was obtained using an MS3000 Malvern laser particle size analyzer.
[0037] Preferably, the filler comprises a surface-treated filler, wherein the surface treatment agent comprises any one or a combination of at least two of silane coupling agents, organosilicon oligomers, and titanate coupling agents, and more preferably silane coupling agents.
[0038] Preferably, the resin composition further comprises 0.01-5 parts by weight of a curing accelerator, wherein the curing accelerator may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 4.8 parts by weight, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0039] Preferably, the curing accelerator includes any one or a combination of at least two of imidazole compounds, Lewis acids, pyridine compounds, organometallic salt compounds, piperidine compounds, tertiary amines, and tertiary phosphorus compounds.
[0040] Preferably, the imidazole compound includes any one or a combination of at least two of 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-undecylimidazole, 2-dodecylimidazole, 2-heptadecanylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4-methylimidazole, and 1-cyanoethyl-2-methylimidazole.
[0041] Preferably, the Lewis acid includes p-toluenesulfonic acid.
[0042] Preferably, the pyridine-based curing accelerator includes pyridine and / or pyridine derivatives (e.g., 4-dimethylaminopyridine).
[0043] Preferably, the organometallic salt compound includes any one or a combination of at least two of the following: octanoic acid metal salt, isooctanoic acid metal salt, acetylacetone metal salt, naphthenic acid metal salt, salicylic acid metal salt, and stearic acid metal salt.
[0044] Preferably, the metal in the organometallic salt compound includes any one or a combination of at least two of zinc, copper, iron, tin, cobalt, and aluminum.
[0045] Preferably, the tertiary amine includes tri-n-butylamine.
[0046] Preferably, the tertiary phosphorus comprises triphenylphosphine.
[0047] Preferably, the resin composition further comprises 2-20 parts by weight of flame retardant, wherein the parts by weight of flame retardant may be 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18 or 20 parts, as well as specific values between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0048] This invention does not specifically limit the flame retardant, and includes halogenated flame retardants (e.g., brominated flame retardants) and / or non-halogenated flame retardants. Exemplarily, the non-halogenated flame retardant includes any one or a combination of at least two of inorganic phosphorus-based flame retardants, organic phosphorus-based flame retardants, and metal compounds.
[0049] Preferably, the resin composition further comprises 0.01-5 parts by weight of coupling agent, wherein the parts by weight of coupling agent may be 0.05 parts, 0.1 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, as well as specific values between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0050] Preferably, the coupling agent comprises a silane coupling agent.
[0051] This invention does not specifically limit the type of silane coupling agent, but includes, by way of example, any one or a combination of at least two of the following: epoxy silane coupling agents, amino silane coupling agents, vinyl silane coupling agents, styryl silane coupling agents, isobutylene silane coupling agents, propylene silane coupling agents, urea silane coupling agents, mercapto silane coupling agents, chloropropyl silane coupling agents, sulfur-based silane coupling agents, and isocyanate-based silane coupling agents.
[0052] Solvents may also be added to the resin composition. The amount of solvent added is selected by those skilled in the art based on experience and process requirements, so that the resin composition reaches a suitable viscosity for use, facilitating coating, impregnation, and processing. During subsequent drying, semi-curing, or complete curing stages, the solvent in the resin composition will partially or completely evaporate.
[0053] The solvent used in this invention is not particularly limited, and generally can be ketones such as acetone, butanone, and cyclohexanone; aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, or butanol; ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, carbitol, and butyl carbitol; and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. The solvent can be used alone or in mixtures of two or more. Preferably, ketones such as acetone, butanone, and cyclohexanone, and aromatic hydrocarbons such as toluene and xylene are used.
[0054] The resin composition provided by the present invention is prepared by the following method, the preparation method comprising: mixing and dispersing the components in the resin composition evenly to obtain the resin composition.
[0055] In a second aspect, the present invention provides a resin film, the material of which comprises the resin composition as described in the first aspect.
[0056] Preferably, the resin film is obtained by coating the resin composition onto a release material and then drying and / or semi-curing it.
[0057] Preferably, the drying and semi-curing temperatures are each independently between 100-180℃, for example, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, or 175℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values included in the range.
[0058] Thirdly, the present invention provides a resin-coated copper foil, the resin-coated copper foil comprising a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in the first aspect.
[0059] Preferably, the resin-coated copper foil is obtained by coating the resin composition onto a copper foil and then drying and / or semi-curing it.
[0060] Preferably, the drying and semi-curing temperatures are each independently between 100-180℃, for example, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃, or 175℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values included in the range.
[0061] Fourthly, the present invention provides a prepreg comprising a substrate and a resin composition as described in the first aspect attached to the substrate.
[0062] Preferably, the resin composition is adhered to the substrate after impregnation and drying.
[0063] Preferably, the raw materials of the substrate include any one or at least two combinations of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers; for example, glass fiber cloth, organic fiber cloth, glass fiber paper, quartz glass fiber blended cloth, non-woven fabric, quartz cloth, wood pulp paper, etc.
[0064] Preferably, the fiberglass cloth includes any one or a combination of at least two of Q-fiberglass cloth, E-fiberglass cloth, D-fiberglass cloth, L-fiberglass cloth, M-fiberglass cloth, S-fiberglass cloth, T-fiberglass cloth, and NE-fiberglass cloth.
[0065] Preferably, the organic fiber cloth includes any one or a combination of at least two of polyimide fiber cloth, polyamide fiber cloth, polyester fiber cloth, polyphenylene ether fiber cloth, and liquid crystal polymer fiber cloth.
[0066] For example, the prepreg is prepared by impregnating a substrate with the resin solution of the resin composition and then drying it to obtain the prepreg.
[0067] Preferably, the solvent of the resin adhesive includes any one or a combination of at least two of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene, and xylene.
[0068] Preferably, the drying temperature is 100-180℃, for example, it can be 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃, 170℃ or 175℃, as well as specific values between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0069] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range.
[0070] Fifthly, the present invention provides a laminate comprising at least one prepreg as described in the fourth aspect.
[0071] In a sixth aspect, the present invention provides a metal foil laminate, the metal foil laminate comprising at least one of the following: a resin film as described in the second aspect, a resin-coated copper foil as described in the third aspect, and a prepreg as described in the fourth aspect.
[0072] Preferably, the metal foil in the metal foil-coated laminate includes any one or a combination of at least two of copper foil, aluminum foil, nickel foil, and alloy foil, with copper foil being more preferred.
[0073] Wherein, the metal foil is copper foil, and the metal foil laminate is copper clad laminate.
[0074] Preferably, the number of prepreg sheets in the metal foil laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, and the specific point values between the above point values are not exhaustively listed in this invention due to space limitations and for the sake of brevity.
[0075] For example, the method for preparing the metal foil laminate includes: pressing a metal foil onto one or both sides of a prepreg and curing it to obtain the metal foil laminate; or, stacking at least two prepregs into a laminate, then pressing a metal foil onto one or both sides of the laminate and curing it to obtain the metal foil laminate.
[0076] Preferably, the curing is carried out in a press.
[0077] Preferably, the curing temperature is 170-280℃, such as 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃ or 270℃, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range, but 200-250℃ is further preferred.
[0078] Preferably, the curing pressure is 10-60 kg / cm². 2 For example, it can be 15kg / cm 2 20kg / cm 2 25kg / cm 2 30kg / cm 2 35kg / cm 2 40kg / cm 2 45kg / cm 2 50kg / cm 2 Or 55kg / cm 2 As well as the specific point values between the above point values, due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values included in the range.
[0079] Preferably, the curing time is 30-300 min, for example 40 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, and specific values between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values included in the range, but 30-180 min is further preferred.
[0080] In a seventh aspect, the present invention provides a printed circuit board, the printed circuit board comprising at least one of the following: a resin film as described in the second aspect, a resin-coated copper foil as described in the third aspect, a prepreg as described in the fourth aspect, a laminate as described in the fifth aspect, and a metal foil-coated laminate as described in the sixth aspect.
[0081] Compared with the prior art, the present invention has the following beneficial effects:
[0082] (1) In the resin composition provided by the present invention, the crosslinking density of the cured product is synergistically improved by the design of the benzoxazine resin with a specific structure and its interaction with the curing agent, epoxy resin and filler, so that the resin composition and the prepreg, laminate and metal foil laminate containing it have low coefficient of thermal expansion, high glass transition temperature and good fluidity. In particular, it effectively improves the fluidity under high filler filling conditions, has excellent processing performance, excellent dielectric properties, and avoids appearance defects such as grooves on the edge of the board.
[0083] (2) Through the design and optimization of the resin composition, the present invention achieves a planar thermal expansion coefficient XY-CTE ≤ 12.6 μm / (m·℃) and a glass transition temperature T of the prepared metal foil laminate. g The dielectric loss tangent D is 195-205℃ and 10GHz. f ≤0.0063, fluidity ≤20%, with both low coefficient of thermal expansion and high T g With excellent processing fluidity and no visible defects such as grooves on the edges of the substrate, it can fully meet the application requirements of high-performance substrate materials. Attached Figure Description
[0084] Figure 1 A plate surface observation view provided in Example 1;
[0085] Figure 2 An observation attempt of the plate surface provided for Comparative Example 1. Detailed Implementation
[0086] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0087] The materials involved in the following specific embodiments of the present invention are as follows:
[0088] (1) Epoxy resin
[0089] NC-3000-H, Biphenylphenolic epoxy resin, Nippon Kayaku Co., Ltd.;
[0090] EPR627M80, Bisphenol A phenolic epoxy resin, Momentive Corporation, USA.
[0091] (2) Curing agent
[0092] Phenolic resin, SN-485, Nippon Steel Chemical Materials Co., Ltd.;
[0093] Dicyclopentadiene-type active ester, HPC-8000-65T, DIC Corporation, Japan.
[0094] (3) Benzoxazine resin
[0095] BOZ1: A benzoxazine resin having the structure shown in Formula II, sourced from Dongcai Company:
[0096]
[0097] Where R1 is *-CH2-*, R2 is *-CH2-*, and n is 5;
[0098] BOZ2: A benzoxazine resin with the structure shown in Formula II above, sourced from Dongcai Company, where R1 is a single bond and R2 is a single bond. n is 5;
[0099] BOZ3: A benzoxazine resin with the structure shown in Formula II above, from Dongcai Company, wherein R1 is a single bond, R2 is *-CH2-*, and n is 8;
[0100] BOZ4: A benzoxazine resin with the structure shown in Formula II above, sourced from Dongcai Company, where R1 is a single bond and R2 is a single bond. n is 10;
[0101] BOZ-D1: Bisphenol A type benzoxazine resin, with the following structure: CB3170, from Chengdu Keyi Company, China;
[0102] BOZ-D2: Bisphenol F type benzoxazine resin, with the following structure: CB4170, from Chengdu Keyi Company, China;
[0103] BOZ-D3: DCPD type benzoxazine resin, with the following structure: LZ8260N70, from HUNTSMAN;
[0104] BOZ-D4: Diaminodiphenylmethane (MDA) type benzoxazine resin, with the following structure: From Shikoku Chemical Co., Ltd.;
[0105] BOZ-D5: ODA type benzoxazine resin, with the following structure: PF-3500 is from Chang Chun Chemical Co., Ltd. in Taiwan, China.
[0106] (4) Packing
[0107] DQ1028L, spherical silica, Jiangsu Lianrui Company, China.
[0108] (5) Curing accelerator
[0109] 4-Dimethylaminopyridine (DMAP), Guangrong Chemical Company.
[0110] (6) Flame retardants
[0111] XZ92741, phosphorus-containing phenolic resin, Olin Corporation.
[0112] (7) Coupling agent
[0113] KBM-403, 3-epoxypropoxypropyltrimethoxysilane, Shin-Etsu Chemical Industry Co., Ltd.
[0114] Examples 1-6, Comparative Examples 1-8
[0115] A resin composition, the types and amounts of each component are shown in Tables 1 and 2, and the unit of amount of each component is "parts".
[0116] A prepreg comprising the resin composition and a metal foil-coated laminate are prepared by the following method:
[0117] (1) Mix and disperse each component of the resin composition with methyl ethyl ketone solvent according to the formula amount to prepare a resin solution with a solid content of 65%.
[0118] (2) Impregnate the fiberglass cloth with the resin solution, and then heat and dry it in a forced-air drying oven at 150°C for 5 minutes to obtain a single weight of 250 g / m. 2 Prepreg;
[0119] (3) Stack two (or six) sheets of prepreg obtained in step (2) together, and press an 18μm thick electrolytic copper foil onto the top and bottom sides of the stack. Then press the stack at 210℃ and 35kg / cm² in a press. 2 After curing for 120 minutes, a metal foil laminate with a core board thickness of 0.25 mm (or 0.75 mm) is obtained. After etching the copper foil of the metal foil laminate, a laminate with a thickness of 0.25 mm (or 0.75 mm) is obtained.
[0120] The performance of the metal foil-coated laminate / laminate is tested using the following specific methods:
[0121] (1) Glass transition temperature T g The test was conducted using a differential scanning calorimeter (DSC) according to the standard specified in IPC-TM-6502.4.25.
[0122] (2) Coefficient of thermal expansion (CTE): The laminate was tested according to the CTE test standard specified in IPC-TM-6502.4.41 using a thermomechanical analyzer (TMA instrument) to obtain the planar coefficient of thermal expansion (XY-CTE).
[0123] (3) Dielectric loss tangent D f According to the standard specified in IPC-TM-650 2.5.5.13, the dielectric loss tangent (D) of the laminate at a test frequency of 10 GHz was measured. f );
[0124] (4) Flowability: The prepreg is tested according to the resin flow percentage of the prepreg in IPC-TM-650 2.3.17;
[0125] (5) Appearance: Etch or peel off the copper foil at the edge of the laminate to expose the substrate. Visually inspect the substrate edge under strong light for defects such as uneven flow or grooves; for example, Figure 1 The surface observation of the board material in Example 1 shows that the glue flow at the board edges is normal and there are no defects such as grooves. Figure 2 As a comparative example, the surface observation of the board material showed obvious groove defects (the texture shown is the groove) on the edge of the board.
[0126] The test results are shown in Tables 1 and 2.
[0127] Table 1
[0128]
[0129]
[0130] Table 2
[0131]
[0132]
[0133] According to the performance data in Table 1, Examples 1-6 of this invention, through the design of multifunctional benzoxazine resin and its interaction with curing agent, epoxy resin, and filler, demonstrate that the benzoxazine resin molecule has a long-chain segment structure, containing more oxazine rings, resulting in a higher crosslinking density with epoxy resin. Simultaneously, the resin contains more benzene rings, leading to greater rigidity of the board. This results in a low coefficient of thermal expansion, a high glass transition temperature, and good flowability under high-filling conditions for the resin composition and its containing prepreg, laminate, and metal foil-coated laminate. It also exhibits excellent processing performance and dielectric properties, and avoids surface defects such as grooves at the edges of the board. Specifically, the laminates of Examples 1-6 have a CTE ≤ 12.6 μm / (m·℃) and a glass transition temperature T0. g ≥195℃, 10GHz dielectric loss tangent Df ≤0.0063, fluidity ≤20%, with both low coefficient of thermal expansion and high T g Excellent processing fluidity, with no visible defects such as grooves on the edges of the sheet.
[0134] Compared to Example 1, Comparative Example 1 used a curing agent for all curing processes and did not use benzoxazine resin. The measured results of the boards show that the Tg of the boards is significantly higher. g At only 155℃, the CTE is 13.8μm / (m·℃), the adhesive sheet has poor fluidity, and the edges of the board have grooves.
[0135] Compared to Example 1, Comparative Example 2 used benzoxazine resin for curing without a curing agent. The measured results of the boards show that the D of the boards... f The value was relatively high at 0.0085, although the flowability of the adhesive sheet was 18%, there were grooves at the edges of the sheet.
[0136] Compared to Example 1, Comparative Example 3 used an excessive amount of benzoxazine resin and an insufficient amount of curing agent. The measured results of the boards show that the D of the boards... f The value is relatively high at 0.0080, although the adhesive sheet has a flowability of 15%, there are grooves at the edges of the sheet.
[0137] Compared to Comparative Examples 1-3, Example 1 used both a curing agent and benzoxazine resin. These two agents have different peak temperatures during epoxy curing. As the temperature increases, the curing agent preferentially reacts with the epoxy resin, increasing the resin's melt viscosity. This increased viscosity promotes the flow of inorganic powder (filler) and resin together, thus preventing grooves from appearing at the edges of the board. At this point, some of the benzoxazine resin has a low degree of reaction and low viscosity, resulting in good flowability of the adhesive sheet. Adjusting the ratio of curing agent to benzoxazine resin allows the adhesive sheet to have good flowability while preventing grooves at the edges of the board. Furthermore, the presence of benzoxazine resin increases the TT of the board. g It reduces the CTE of the board material.
[0138] Compared with Example 4, Comparative Example 4 used bisphenol A type benzoxazine resin. The measured results of the boards show that the T... g The temperature was relatively low at 163℃, and the CTE was 13.6 μm / (m·℃).
[0139] Compared with Example 5, Comparative Example 5 used bisphenol F type benzoxazine resin. The measured results of the boards show that the T... g The temperature was relatively low at 166℃, and the CTE was 13.5 μm / (m·℃).
[0140] Compared with Example 6, Comparative Example 6 used DCPD type benzoxazine resin. The measured results of the boards show that the Tg of the boards is significantly higher. g The temperature was relatively low at 162℃, and the CTE was 13.1 μm / (m·℃).
[0141] Comparative Example 7 used MDA-type benzoxazine resin. The measured results of the boards show that the T... g The temperature was relatively low at 168℃, and the CTE was 13.2 μm / (m·℃).
[0142] Comparative Example 8 used ODA-type benzoxazine resin. The measured results of the boards show that the T... g The temperature was relatively low at 160℃, and the CTE was 13.7 μm / (m·℃).
[0143] The applicant declares that the above embodiments illustrate the resin composition, metal foil laminate, and their applications, but the present invention is not limited to the above process steps, i.e., it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that, The resin composition comprises the following components in parts by weight: The benzoxazine resin has the structure shown in Formula I: R1 and R2 are each independently selected from any one of the following: single bond, unsubstituted or halogen-substituted C1-C12 straight-chain or branched alkylene, C3-C12 cycloalkylene, -O-, -S-, carbonyl, sulfone, and sulfoxide. n is 1-12.
2. The resin composition according to claim 1, characterized in that, The benzoxazine resin has the structure shown in Formula II: Among them, R1, R2, and n have the same limited range as Equation I; Preferably, R1 is selected from any one of single-bonded, unsubstituted, or halogen-substituted C1-C6 straight-chain or branched alkylene groups, or sulfone groups, with single-bonded groups being more preferred. Where -* represents the linking site of the group; Preferably, R2 is selected from any one of single bonds, unsubstituted or halogenated C1-C6 straight-chain or branched alkylene groups, C5-C12 cycloalkylene groups, -O-, and -S-, and more preferably single bonds, *-CH2-* ... -O-; where -* represents the linking site of the group.
3. The resin composition according to claim 1 or 2, characterized in that, The epoxy resin includes any one or a combination of at least two of the following: bisphenol A type epoxy resin, bisphenol F type epoxy resin, phosphorus-containing epoxy resin, isocyanate modified epoxy resin, phenolic epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, naphthalene-containing epoxy resin, and alicyclic epoxy resin. Preferably, the curing agent includes any one or a combination of at least two of phenolic curing agents, cyanate ester curing agents, reactive ester curing agents, polyphenylene ether curing agents, maleimide curing agents, acid anhydride curing agents, and amine curing agents; more preferably, any one or a combination of at least two of phenolic curing agents, reactive ester curing agents, and amine curing agents. Preferably, the phenolic curing agent includes phenolic resin, and more preferably includes any one or a combination of at least two of bisphenol A type phenolic resin, phosphorus-containing phenolic resin, phenolic resin, biphenyl type phenolic resin, dicyclopentadiene type phenolic resin, and naphthol-containing phenolic resin. Preferably, the filler comprises any one or a combination of at least two of the following: silica, hollow filler, alumina, mica, quartz powder, clay, calcium oxalate, calcium carbonate, barium sulfate, magnesium oxide, zinc oxide, boron nitride, aluminum nitride, silicon nitride, aluminum hydroxide, titanium dioxide, glass powder, talc, silicon carbide, barium sulfate, barium titanate, strontium titanate, and calcium silicate.
4. The resin composition according to any one of claims 1-3, characterized in that, The resin composition further includes 0.01-5 parts by weight of a curing accelerator; Preferably, the curing accelerator comprises any one or a combination of at least two of imidazole compounds, Lewis acids, pyridine compounds, organometallic salt compounds, piperidine compounds, tertiary amines, and tertiary phosphorus compounds; Preferably, the resin composition further comprises 2-20 parts by weight of flame retardant; Preferably, the resin composition further comprises 0.01-5 parts by weight of coupling agent; Preferably, the coupling agent comprises a silane coupling agent.
5. A resin film, characterized in that, The resin film is made of the resin composition as described in any one of claims 1-4; Preferably, the resin film is obtained by coating the resin composition onto a release material and then drying and / or semi-curing it.
6. A resin-coated copper foil, characterized in that, The resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the resin composition as described in any one of claims 1-4.
7. A prepreg, characterized in that, The prepreg comprises a substrate and a resin composition as described in any one of claims 1-4 attached to the substrate; Preferably, the resin composition is adhered to the substrate after impregnation and drying.
8. A laminate, characterized in that, The laminate comprises at least one sheet of prepreg as described in claim 7.
9. A metal foil-coated laminate, characterized in that, The metal foil laminate includes at least one of the resin film as described in claim 5, the resin-coated copper foil as described in claim 6, and the prepreg as described in claim 7.
10. A printed circuit board, characterized in that, The printed circuit board includes at least one of the following: the resin film as described in claim 5, the resin-coated copper foil as described in claim 6, the prepreg as described in claim 7, the laminate as described in claim 8, and the metal foil-coated laminate as described in claim 9.
Citation Information
Patent Citations
Halogen-free and phosphorus-free epoxy resin compositions and prepregs and laminates made therefrom
CN102276961A
Curable resin composition, film, prepreg, and cured product
JP2014148562A